EP508 Could microsatellite instability predict the response to immunotherapy in high-grade endometrial carcinomas?. (1st November 2019) - Doulgeraki, T; Vagios, S; Yiannou, P; Giannikaki, E; Papadimitriou, C; Rodolakis, A; Kavoura, E; Vlachos, A; Pavlakis, K
Abstract : Introduction/Background: The recent food and drug administration (FDA) approval of immunotherapy for all microsatellite unstable carcinomas, has strengthen the need for more detailed studies, in order to highlight the group of endometrial cancers that would probably favor from thisnew therapeutic option. One of the hallmarks of carcinomas with microsatellite instability (MSI), is the increased neo-antigen load which leads to an enhanced immune environment. Our goal was to evaluate by immunohistochemistry, whether mismatch repair (MMR) status was related to CD8 high intratumoral infiltration and PD-L1 expression in a series of high-grade endometrial carcinomas and correlate it with several clinicopathological characteristics and with survival. Methodology: The cohort comprised 40 high grade endometrioid, 36 serous, 4 clear cell, 5 unclassified and 7 mixed carcinomas as well as 8 Malignant Mixed Mullerian tumors. All patients were fully surgically staged. Postoperative treatment varied according to the tumor's characteristics. Immunohistochemistry for MLH1, MSH2, MSH6, PMS2, CD8 and PD-L1 was performed. Results: MMR deficient tumors were strongly related to endometrioid type carcinomas (p<0, 001), high CD8 counts (p=0, 015), positive PD-L1 tumors (p=0, 029) and deep myometrial invasion (p=0, 014). Nevertheless, when CD8+ and PD-L1 high tumors were grouped together, they were statistically related to MMR deficiency irrespective of tumor sub-type whereas combined CD8+/PD-L1 low expression was statistically associated with MMR proficient tumors. Both in Kaplan-Mayer univariate and in multivariate analysis, only high CD8+ cells were related to longer progression free survival (p=0, 006 and p=0, 008 respectively)). Conclusion: In high grade endometrial carcinomas, both of endometrioid and of non-endometrioid type, a high CD8+ microenvironment represents an independent favorable prognostic factor for progression free survival. The significant statistical relation of MMR deficient tumors with high intratumoral CD8 counts and positive PD-L1 expression might imply that therapy with immune checkpoint inhibitors could be effective in high grade endometrial carcinomas featuring microsatellite instability. Disclosure: Nothing to disclose.